2017
DOI: 10.1108/ijlls-12-2016-0056
|View full text |Cite
|
Sign up to set email alerts
|

Perceived professional knowledge and competence of mathematics specialists and its development in China

Abstract: Purpose The purpose of this paper is to explore what professional knowledge and competence (PKC) that knowledgeable others, namely, mathematics teaching research specialists (MTRS) in China, need to know, and how they may develop their PKC. Design/methodology/approach This study adopts mixed methods. A survey on PKC with 549 MTRS is utilized to examine MTRS’ perceived held and ideal PKC and perceived effective ways of developing their PKC. The responses to the open-ended questions on the survey were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Through a large scale survey from an insiders' perspective, Huang, Zhang, Mok, Zhao, Zhou and Wu (2017) examined the professional knowledge and competence (PKC) possessed and developed by those knowledgeable others in CLS. The authors found that the ideal PKC structure should have two components: knowledge about teaching and learning as well as competence in mentoring and educational leadership; and knowledge about content, assessing student learning, and use of technology.…”
Section: Major Themes Of This Special Issuementioning
confidence: 99%
“…Through a large scale survey from an insiders' perspective, Huang, Zhang, Mok, Zhao, Zhou and Wu (2017) examined the professional knowledge and competence (PKC) possessed and developed by those knowledgeable others in CLS. The authors found that the ideal PKC structure should have two components: knowledge about teaching and learning as well as competence in mentoring and educational leadership; and knowledge about content, assessing student learning, and use of technology.…”
Section: Major Themes Of This Special Issuementioning
confidence: 99%